Antimicrobial Resistance, Virulence Determinants, and Biofilm Formation of Enterococcus Species From Ready-to-Eat Seafood - Igbinosa, Etinosa O.; Beshiru, Abeni (Frontiers in Microbiology, 2019)
Enterococcus species form an important population of commensal bacteria and have been reported to possess lots of virulence factors considered significantly important in exacerbating diseases which results from them. The present study was designed to characterize antibiotic-resistant and virulent enterococci from ready-to-eat (RTE) seafood. A total of 720 RTE shrimp samples comprising sauced shrimp (n=288), boiled shrimp (n=216) and smoked shrimp (n=216) obtained from open markets in Delta State Nigeria were assessed. Standard classical methods and polymerase chain reaction (PCR) was used in identifying the Enterococcus species. Potential virulence factors (β-haemolysis, gelatinase activity, S-layer and biofilm formation) were assessed using standard procedures. Antibiotic susceptibility profile of the identified enterococci isolates were assayed using Kirby-Bauer disc diffusion method. PCR was further used to screen selected antibiotic resistance and virulence genes. Prevalence of Enterococcus species from shrimp varieties include sauced 26(9.03%), boiled 6(2.78%) and smoked 27(12.50%) with an overall prevalence of 59(8.19%) based on the occurrence of black hallow colonies after incubation. Enterococcus species detected includes E. faecalis 17(28.8%), E. faecium 29(49.2%), E. gallinarum 6(10.2%), E. casseliflavus 2(3.4%), E. hirae 3(5.1%) and E. durans 2(3.4%). Biofilm occurrence amongst the shrimp varieties includes 19/26(73.1%) for sauced shrimps, 5/6(83.3%) for boiled shrimps and 16/27(59.3%) for smoked shrimps. The phenotypic expression of the enterococci virulence revealed: S-layer 59(100%), gelatinase production 19(32.2%), and β-haemolysis 21(35.6%). An average of 3 – 11 virulence genes were detected in the Enterococcus species. The resistance profile of Enterococcus species is a follows: erythromycin 29(49.2%), vancomycin 22(37.3%), and tetracycline 27(45.8%). The frequency of occurrence of antibiotic resistance genes from the phenotypic resistant enterococci isolates to the macrolide, glycopeptide and tetracycline antibiotics is as follows: ermA 13/29(44.8%), vanA 14/22(63.6%), tetA 14/27(51.9%), tetM 15/27(55.6%), ermB 4/29(13.8%) and vanB 5/22(22.7%). Findings from this study reveal the antibiotic resistance of enterococci strains of such species as E. durans, E. casseliflavus, E. gallinarum and E. hirae. This study further revealed that RTE food products are reservoirs of potential virulent enterococci with antibiotic-resistant capabilities. This provides useful data for risk assessment and indicates that these foods may present a potential public health risk to consumers.